Предмет: Математика,
автор: Аноним
Помогите пожалуйста. Желательно на листочке.
Приложения:
Ответы
Автор ответа:
0
г) b² + 2b√m + m
д) k - 2√(kp) + p
е) 3 - 2√18 + 6 = 9 - 6√2
в) 1 - 4√3 + 12 = 13 - 4√3
г) 45 + 12√50 + 40 = 95 + 60√2
д) k - 2√(kp) + p
е) 3 - 2√18 + 6 = 9 - 6√2
в) 1 - 4√3 + 12 = 13 - 4√3
г) 45 + 12√50 + 40 = 95 + 60√2
Автор ответа:
0
(b+√m)^2=b^2+2b√m+m
(√k-√p)^2=k-2√k√p+p
(√3-√6)^2=3-2√3√6+6=9-2√9×2=9-6√2
(1-2√3)^2=1-2×1×2√3+12=13-4√3
(√k-√p)^2=k-2√k√p+p
(√3-√6)^2=3-2√3√6+6=9-2√9×2=9-6√2
(1-2√3)^2=1-2×1×2√3+12=13-4√3
Похожие вопросы
Предмет: Физика,
автор: madadov269
Предмет: Русский язык,
автор: umirzakmuhammedzan66
Предмет: Физика,
автор: pirrat35
Предмет: Математика,
автор: Eeoneliy
Предмет: Математика,
автор: Olgamoskoy